2018
DOI: 10.3390/molecules24010112
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization for Ultrasound-Assisted Extraction and Antioxidant Activity of Flavonoids from Sophora flavescens Using Response Surface Methodology

Abstract: The ultrasonic-assisted extraction process and antioxidant activity of flavonoids from Sophora flavescens were investigated in this study. In order to optimize the extraction of flavonoids from Sophora flavescens, the influence of extraction time, methanol concentration, ultrasonic temperature, and solvent-to-material ratio was analyzed. Results showed that the extraction yields reached a maximum with the extraction time of 30 min, methanol concentration of 80%, temperature of 80 °C, and solvent-to-material ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…is result indicated that the developed RSM model is practicable and can be used to describe the relationship between extraction factors and TFC in the ultrasound-assisted extraction of flavonoids from C. hindsii leaves. In addition, the TFC obtained in this study was found to be comparable to that in tomato pulp (21.52 mg QE/g) [33] and much higher than that in Dysphania ambrosioides (0.06 mg QE/g) [34] and other medicinal plants [35,36]. e study suggests that C. hindsii leaves are a promising source of flavonoids and the ultrasound-assisted extraction is an efficient process for extracting flavonoids from C. hindsii leaves to maximize TFC in a short extraction time and low temperature.…”
Section: Obtaining Optimal Extraction Conditionssupporting
confidence: 53%
See 1 more Smart Citation
“…is result indicated that the developed RSM model is practicable and can be used to describe the relationship between extraction factors and TFC in the ultrasound-assisted extraction of flavonoids from C. hindsii leaves. In addition, the TFC obtained in this study was found to be comparable to that in tomato pulp (21.52 mg QE/g) [33] and much higher than that in Dysphania ambrosioides (0.06 mg QE/g) [34] and other medicinal plants [35,36]. e study suggests that C. hindsii leaves are a promising source of flavonoids and the ultrasound-assisted extraction is an efficient process for extracting flavonoids from C. hindsii leaves to maximize TFC in a short extraction time and low temperature.…”
Section: Obtaining Optimal Extraction Conditionssupporting
confidence: 53%
“…Regardless of strong activity, synthetic antioxidants may cause harmful side effects and hence the exploration for natural antioxidants has been immensely reinforced in recent years. In the previous studies, plant flavonoids have been shown to own robust antioxidant effects [35,36]. Because oxidative stress is a noticeably complicated process, different assays were used in examining the antioxidant effect of C. hindsii leaf extract.…”
Section: Antioxidant Activities Of the C Hindsii Leaf Extractsmentioning
confidence: 99%
“…p-values and F-values are used to verify the significance between coefficients. Specifically, Prob > F values less than 0.01 or 0.05 indicate that coefficients of the model are significant, and the values more than 0.05 indicate that coefficients of the model are not significant [29,30]. Therefore, F Value of 63.77 and Prob > F of less than 0.01 show that the model is significant, and there is only a 0.01% chance of such a large "Model F-value" due to noise in the model.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…However, when the ultrasonic time was long, the obtained crude extract could be adsorbed back to the soil with the influence of soil-water partition coefficients, resulting in decreased recoveries [43,44]. This declining trend may also be because the prolonged ultrasonic time can degrade the extraction targets or accompany the dissolution of other impurities [45]. The highest recoveries (76.50% and 83.68%) appeared at 30 min.…”
Section: Ultrasonication Timementioning
confidence: 99%
“…The volume of the extraction buffer (10,20,30,40, and 50 mL), the pH of the extraction solution (3, 4, 5, 6, and 7), the ultrasonic temperature (15,25,35,45, and 55 • C), ultrasonic time (10, 20, 30, 40, 50 min), and the frequency of extraction (1, 2, 3, 4 and 5) were explored in this part. The effect of the single factor was tested with all other factors kept constant, and the experimental results were repeated three times.…”
Section: Single-factor Experimentsmentioning
confidence: 99%